Inflammatory bowel disease – one entity with many molecular faces - Sylwia Szymańska; Malgorzata Matuszczyk; Magdalena Osuch; Monika Meglicka; Edyta Szymanska; Joanna Bierła; Jaroslaw Kierkuś (Gastroenterology Review)
Inflammatory bowel disease (IBD) is a heterogenous group of chronic inflammations in the gastrointestinal tract, which traditionally consists of two types: Crohn’s disease and ulcerative colitis. They differ when it comes to clinical, endoscopic, and histopathological changes. The exact aetiology of IBD has not been fully comprehended, but what is known so far is that the aetiopathogenesis of the disease is compound. Many articles have been written on the cellular/molecular background of IBD. Based on various molecular pathways, new forms of the disease have been discovered, including very early-onset IBD (VEO-IBD) or IBD coexisting with primary sclerosing cholangitis. The aim of this article is to present the molecular mechanisms leading to IBD, focusing on new forms of this disorder.